Anthropometric evaluation of cockpit designs. Issue 2 (2nd April 2016) - Şenol, Mehmet Burak
Abstract : The objective of this research is to evaluate all the critical reaches in a cockpit and determine the visual sufficiency of a cockpit to accommodate 90% of potential pilots. While mismatches of measurements with cockpit dimensions are revealed, proposals are made to improve cockpit ergonomics. Regression models were generated to predict and assure adequate exterior vision. Mean, lower and upper control limits of all measurements were found acceptable except eye level. There are very strong positive relationships between stature and eye level ( R 2 = 0.972, p < 0.01), and eye level and visual angle ( R 2 = 0.994, p < 0.01). Display panel height should be at least 1.645 × SD smaller than the eye level mean or seating adjustment limits in height may be changed. In general, cockpit design is acceptable in terms of fit/reach accommodation for pilots, except eye level and visual variables that could be solved by better seat adjustments.